ANALISIS INTEROPERABILITY AIR & MARITIME SURVEILLANCE SYSTEM DALAM OPERASI KEAMANAN LAUT GABUNGAN TNI AL-TNI AU DI PERAIRAN INDONESIA - Handyka Pramahendarta (Faculty of Science and Technology University of Pramita Indonesia, 2023)
Law of the Republic of Indonesia Number 34 of 2004 concerning the Indonesian National Army (TNI) which has the main task of upholding state sovereignty, maintaining the territorial integrity of the Unitary State of the Republic of Indonesia based on Pancasila and the Constitution of the Republic of Indonesia Year 1945, and protecting the entire nation and all Indonesian bloodshed from threats anddisturbances to the integrity of the nation and state. In accordance with its duties, the TNI has the responsibility to: maintaining the security of Indonesian waters in order to maintain the sovereignty of the Republic of Indonesia, Currently security in Indonesian territorial waters is still not optimal because several violations are still found in Indonesian territorial waters. In this case, air interoperability & maritime surveillance system is needed, to improve interoperability in the implementation of the main tasks of the TNI. This study was conducted to analyze the Interoperability Air & Maritime Surveillance System in joint maritime security operations in Indonesian waters. The methodology used in this study is qualitative research. The results of the Air & Maritime Surveillance System Interoperability Analysis research in joint maritime security operations in Indonesian waters are that the security conditions in Indonesian waters are currently quite safe but there are still violations needed to improve the Air & Maritime Surveillance System Interoperability with improved infrastructure and facilities, making Interoperability Procedures and forming an organizational model, namely Maritime Operations Centers (MOCs) for achieve the goal of realizing the security of Indonesian waters.